The Analyze of Nation Leader’s Decision-Making Based on Young Generation Perception - Rambe, Kamarul Zaman; Andriyanty, Reny (Technium Social Sciences Journal, 2021)
The objectives of this study to examine the significance of relationship between the characteristics of the president of the Republic of Indonesia, the president’s decision making and the president’s changing responds on development performance in Indonesia based on young generation cohort. Through this research, will be obtained the recommendation for the formulation of an ideal national leader model according to the times. This research implements a descriptive method. The datas were analyzed using structural equations. The character of the president is not confirmed that it have a significant direct and indirect correlation with development performance. There decision making pattern corelated with development performance at the 10 percent significance level. Decision making by the president is based on successive factors, they are as follow: group decision making, decision making with Delphi techniques and participatory decision making. The analysis of the changing response was confirmed to have a relationship with the development performance at a significance level of 10 percent. Sensitivity factors that have a substantial influences are: technological changes respond, sensitivity to national & global economic changes respond, and sensitivity to social respond change and sensitivity to respond change in general.